Interleukin-18 as a Biomarker of Subclinical Lupus Nephritis - Samah Abdel Rahman EL BAKRY; AbdelAzim Mohamed ALHEFNY; Dina Shawky AL-ZIFZAF; Ola Hasan NADA; Rania Hamdy EL KABARITY; Khaled OMAR (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the relationship between serum interleukin-18 (IL-18) and its renal expression with histological classification of lupus nephritis in patients with insignificant proteinuria, and evaluate serum IL-18 as a biomarker of subclinical renal involvement in lupus patients. Patients and methods: Forty lupus patients (5 males, 35 females; mean age 26.3±7.9 years; range 16 to 52 years) with proteinuria less than 0.5 g/24 hours and 20 healthy controls (2 males, 18 females, mean age 25.5±6.3 years; range 16 to 49 years) were included. Patients underwent full history taking, thorough clinical examination, assessment of disease activity, measurement of serum IL-18, and renal biopsies for histopathological assessment and immunostaining for tissue expression of IL-18. Results: Lupus patients had significantly higher serum IL-18 levels than controls (612.4 and 209.3 pg/mL, respectively; p<0.01). Serum IL-18 was significantly higher in patients with classes III, IV and V lupus nephritis (609.1, 833.1 and 790 pg/mL, respectively) than in patients with class I and II (370 and 476.8 pg/mL, respectively). Immunostaining of IL-18 showed glomerular expression in classes IV and V, glomerular and tubular infiltration in class III, tubular pattern in class II and no staining in class I. Patients with diffuse glomerular IL-18 staining had higher levels of serum IL-18 than those with no staining (840.8 and 522.9 pg/mL, respectively; p=0.0). Those with diffuse tubular IL-18 staining had higher levels of serum IL-18 than those with no staining (514.2 and 393 pg/mL, respectively; p<0.05). Serum IL-18 correlated with serum creatinine and the activity index of renal biopsies. Conclusion: IL-18 may play a role in the pathogenesis of lupus nephritis. Results of this study showed that serum IL-18 reflects the extent of renal injury in lupus even in absence of significant proteinuria regardless of the level of disease activity; proposing its early role in pathogenesis of lupus nephritis. Thus serum IL-18 can be used as a biomarker that distinguishes the different histological classes of subclinical lupus nephritis.